Nature of slab-mantle interactions recorded by coupled δ13C–δ15N–δ18O signatures and elemental compositions of Koidu diamonds and their inclusions. (15th April 2023) - Lai, Mei Yan; Stachel, Thomas; Stern, Richard A.; Li, Kan; Pearson, D. Graham; Harris, Jeff W.
Abstract: Eclogitic diamond formation can be associated with interactions between subducted slabs and ambient mantle. To gain a better understanding of the extent of chemical exchange between slabs and ambient mantle and the mechanisms of coeval diamond formation, we examined 16 diamonds with eclogitic garnet inclusions from the Koidu kimberlite complex in Sierra Leone (West African Craton). We analyzed the 16 garnet inclusions for major element, trace element and oxygen isotope (δ 18 O) compositions and their host diamonds for carbon (δ 13 C) and nitrogen (δ 15 N) isotope compositions. The garnet inclusions have δ 18 O values ranging from +5.4 to +12.1‰ (median = +11.3‰) and all but two have δ 18 O values ≥+9.9‰. Such high δ 18 O values indicate a link to protoliths that had undergone extensive low-temperature alteration by seawater, which occurs in the uppermost basaltic layer of oceanic crust, prior to subduction. Diamonds hosting the high δ 18 O garnets have a crustal δ 13 C signature (−29.6 to −19.4‰) paired with δ 15 N values (−5.6 to +1.3‰, with one outlier at +9.9‰) implying typically only minor 15 N enrichment. This apparent decoupling of δ 18 O and δ 13 C from δ 15 N indicates diamond formation in an eclogitic substrate where garnet oxygen isotope compositions are inherited from altered low-pressure protoliths, diamond carbon is principally derived from biogenic carbonate and organic matter, and diamond nitrogen is variably added by an external, mantle-derived fluid that prompted diamond formation. Of the two remaining garnet inclusions, one has mantle-like δ 18 O (+5.4‰) and a positive Eu anomaly, suggesting derivation from gabbroic protoliths originally located deep in the oceanic crust where significant alteration by seawater did not occur. Based on mantle-like δ 13 C (−4.7‰) and δ 15 N (−6.9‰), the associated diamond formed from mantle-derived fluids/melts. Relative to the other Koidu garnet inclusions, the final garnet has a small majorite component (formation pressure ∼8 GPa), high Mg# (79.0), elevated Cr# (0.90), and low δ 18 O (+6.3‰), suggesting encapsulation during infiltration of slab-derived melts into surrounding asthenospheric peridotite, associated with a high degree of chemical exchange between slab- and mantle-derived components.